O MUNICÍPIO COMO LUGAR ‘OUTRO’ A PARTIR DA REFORMA SANITÁRIA - UBESSI, LIAMARA D.; BERLEZI, JOÃO J.; MIX, PAULO R.; BAZOTTI, KELLEN V.; PASCHE, DÁRIO F.; RIGHI, LIANE B. (Salão do Conhecimento, 2013)
Resumo